High-strength and high-toughness polylactic acid wire for 3D printing and preparation method of high-strength and high-toughness polylactic acid wire
By adding PBAT, titanate, triethyl citrate and talc to the PLA material, a specific preparation method is used to solve the problem of insufficient mechanical properties of PLA materials under high load or high impact force, and the preparation of high-strength and high toughness polylactic acid silk is achieved, which improves the mechanical properties and processing properties of the materials.
Patent Information
- Application Number
- CN202411426691.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-04-22
AI Technical Summary
In the application of high load or high impact force, existing PLA materials have insufficient mechanical properties and are prone to cracking or deformation, and the toughness of PBAT modified PLA materials is low.
High-strength and high-toughness polylactic acid wire is prepared by vacuum oven drying, high-speed mixer mixing, spraying solution and adding talc powder, vacuum drying, twin-screw extruder blending and drawing molding.
It significantly improves the mechanical properties of polylactic acid, increases the elongation of break and impact strength of the material, overcomes the problems of brittleness of PLA materials and the low toughness of PBAT modified PLA materials, excellent printing performance, simple operation, reduces production costs, and is easy to produce in industrial use.
Smart Images

Figure CN119859392A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of 3D printing, and in particular relates to a high-strength and high-toughness polylactic acid filament for 3D printing, and also relates to a preparation method of the polylactic acid filament. Background Art
[0002] 3D printing technology, also known as additive manufacturing technology, is an advanced manufacturing method based on digital models to manufacture three-dimensional physical objects by stacking metals, polymers and other adhesive materials layer by layer. The advancement of this technology has not only promoted the transformation of the manufacturing industry, but also opened up a variety of application fields. With the development of technology, the types and performance of 3D printing materials are also constantly improving. Among them, polylactic acid (PLA), as a biodegradable polymer material, has become an important research object in the field of 3D printing because of its abundant sources, renewable and environmentally friendly. The advantages of polylactic acid include low melting point, good processing performance and good biodegradability, which makes it widely used in 3D printing. However, the mechanical properties of traditional PLA filaments often cannot meet the requirements in some high-load or high-impact applications. PLA itself has low impact toughness and fracture strength, which makes its printed parts prone to cracking or deformation when subjected to force or impact. This problem is particularly prominent in application scenarios that require high strength and high toughness, such as engineering parts, functional prototypes and structural parts. These application areas require materials to have excellent mechanical properties and durability while maintaining light weight.
[0003] To solve these problems, researchers have invested a lot of effort in modifying PLA to improve its mechanical properties. Common modification methods include adding fillers, blending modification and chemical modification. For example, the Chinese invention patent with application date of November 29, 2013 and publication number of CN103665802 A discloses a material modification method that can be used for printing. The method uses inorganic nanomaterials as toughening agents to perform toughening modification. Although the method can enhance the toughness of polylactic acid, the addition of inorganic nanoparticles causes the polylactic acid system to be not uniform enough, and the processing performance is significantly reduced, which is not conducive to production and affects product molding. The Chinese invention patent with application date of February 23, 2017 and application number of CN201710100360.2 discloses a reaction extrusion toughened carbon fiber reinforced polylactic acid printing material and its preparation method. The method adopts reaction extrusion toughening technology, which effectively solves the problem of poor toughness and low elongation at break of wire material with high carbon fiber content, improves the interface compatibility between carbon fiber and polylactic acid, and ensures the smooth progress of the printing process. However, the operation is cumbersome and the cost is high, which is not conducive to industrial production. For another example, the Chinese invention patent with application date of October 24, 2019 and application number CN201911018965.2 proposes a toughened modified PLA printing filament material and a preparation method thereof. The method toughens and modifies PLA through melt blending technology, and uses an extruder to prepare modified PLA filaments with excellent performance. The filament material has significant improvements in elasticity, flexibility and impact resistance, overcomes the shortcomings of pure PLA filament materials, and provides a new solution for the development of printing technology. However, the degradation performance of polylactic acid during multiple processing is ignored.
[0004] The above research and innovation provide valuable references for improving the performance of PLA and expanding its application range, especially in the fields of industrial products, daily necessities and biomedicine. However, although the existing modification methods have a certain improvement effect, there are still challenges in the balance of additive dosage, processing stability and material performance. The existing PLA materials are prone to wrinkle structures when printed, and the toughness of the PLA materials modified with PBAT is low. Future research should focus on further optimizing the modification methods of PLA to better meet the needs of the industrial and biomedical fields for high-performance 3D printing materials and promote the advancement and application development of this technology. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength and high-toughness polylactic acid filament for 3D printing, which solves the problems in the prior art that PLA materials are not smoothly printed, are easy to draw, are easy to warp, are easy to have a wrinkled structure, and that the toughness of the PLA materials modified by PBAT is low.
[0006] The second object of the present invention is to provide a method for preparing the high-strength and high-toughness polylactic acid filament for 3D printing.
[0007] The first technical solution adopted by the present invention is: The high-strength and high-toughness polylactic acid filament for 3D printing includes the following components, calculated by mass percentage: PLA 89~89.6wt%, PBAT 4.5~4.9wt%, titanate 2.7~4.3wt%, triethyl citrate 1.7~2.3wt% and talc 2.3~3.5wt%.
[0008] The second technical solution adopted by the present invention is a method for preparing high-strength and high-toughness 3D printed polylactic acid filaments, and the specific method is as follows: S1. Place PLA and PBAT in a vacuum oven and dry them; S2, mixing equal amounts of titanate and triethyl citrate in deionized water to form a mixed solution, and adjusting the pH to 5.5-6 with acetic acid to obtain S solution; S3, mixing the PLA and PBAT dried in S1 in a high-speed mixer, spraying the S solution during the mixing process, and continuously adding talcum powder to make it adhere to the surface of the particles, and continuously stirring until uniform, to obtain a granular material; S4, drying the granular material obtained in S3 in a vacuum box to obtain dry granular material; S5. The dried granular material is placed in a desktop twin-screw extruder for blending, extrusion and wire drawing to obtain high-strength and high-toughness polylactic acid filaments for 3D printing.
[0009] The present invention is also characterized in that: The drying temperature in the vacuum oven in S1 is 70-90°C, and the drying time is 12-15h.
[0010] The concentration of titanate in the S solution is 0.06 g / ml~0.12 g / ml, the concentration of triethyl citrate is 0.06 g / ml~0.12 g / ml, and the concentration of acetic acid is 97%~99.8%.
[0011] In S3, based on parts by weight, PLA is 85-95 parts by weight, PBAT is 5-20 parts by weight, talc is 1-5 parts by weight, titanate is 2-3 parts by weight, and triethyl citrate is 2-3 parts by weight.
[0012] In S3, the stirring speed is 400-600 rpm, and the stirring time is 2-3 h.
[0013] The drying temperature in the vacuum box of S4 is 70~80℃, and the drying time is 1~2h.
[0014] The screw speed of the twin-screw extruder in S5 is 30~40 rpm, the screw speed during feeding is 25~35 rpm, the temperature of the extruder feeding port is 160~170 ℃, the temperature of the middle area of the extruder is 185~195 ℃, and the temperature of the extruder head is 190~195 ℃.
[0015] The beneficial effects of the present invention are: (1) The method for preparing high-strength and high-toughness polylactic acid filaments for 3D printing of the present invention can effectively increase the impact toughness and melt flow rate of the material by using talcum powder as an inorganic filler, and using a copolymer of polybutylene terephthalate (PBAT) as a toughening agent, and using a melt blending method to modify the polylactic acid, thereby changing the brittleness of PLA, reducing the stiffness of the material, and increasing the elongation at break and impact strength of the material. The material can withstand a large degree of deformation without destroying the structure of the material, and has good mechanical properties; triethyl citrate is added as a plasticizer, and titanate is used as a coupling agent, which can enhance the flexibility of the material while improving its interfacial compatibility, so that the strength and toughness can be synergistically improved; (2) The high-strength and high-toughness polylactic acid filament for 3D printing prepared by the present invention has excellent performance of the printed product, overcoming the poor toughness and processing performance defects of the existing 3D printing polylactic acid materials, simple operation, reduced production costs, and easy industrial production, solving the problems of the prior art that the PLA materials are not smooth in printing, easy to draw, easy to warp, easy to have wrinkled structures, and the low toughness of the PBAT-modified PLA materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The DSC temperature rise curves of the polylactic acid filaments obtained in Examples 1 to 3 of the preparation method of the present invention are shown. DETAILED DESCRIPTION
[0017] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0018] The high-strength and high-toughness polylactic acid filament for 3D printing includes the following components, calculated by mass percentage: PLA 89~89.6wt%, PBAT 4.5~4.9wt%, titanate 2.7~4.3wt%, triethyl citrate 1.7~2.3wt% and talc 2.3~3.5wt%.
[0019] The preparation method of high-strength and high-toughness polylactic acid filament for 3D printing is as follows: S1. Place PLA and PBAT in a vacuum oven and dry them; Among them, the vacuum oven drying temperature is 70~90℃, and the drying time is 12~15h.
[0020] S2, mixing equal amounts of titanate and triethyl citrate in deionized water to form a mixed solution, and adjusting the pH to 5.5-6 with acetic acid having a concentration of 97%-99.8% to obtain an S solution; Among them, the concentration of titanate is 0.06g / ml~0.12g / ml, and the concentration of triethyl citrate is 0.06g / ml~0.12g / ml.
[0021] S3, mix the PLA and PBAT dried in S1 in a high-speed mixer, spray the S solution evenly during the mixing process, add talcum powder while spraying, stir at a speed of 400-600 rpm, stir for 2-3 hours, and continue stirring until completely uniform after spraying to obtain granular material; In the whole process, based on weight parts, PLA is 85-95 weight parts, PBAT is 5-20 weight parts, talc is 1-5 weight parts, titanate is 2-3 weight parts, and triethyl citrate is 2-3 weight parts.
[0022] S4. Dry the granules obtained in S3 in a vacuum oven at 70-80°C for 1-2 hours to obtain dry granules.
[0023] Here, since moisture will affect the performance of polylactic acid, it is dried in a vacuum oven.
[0024] S5, placing the dry filler in a twin-screw extruder for blending, extrusion and wire drawing to obtain a high-strength and high-toughness 3D printed polylactic acid filament; The screw speed in the twin-screw extruder is 30~40 rpm, and the screw speed during feeding is 25~35 rpm. The temperature setting of the extruder is divided into three areas from the feeding port to the extruder head, which are set to 160~170 ℃ at the feeding port, 190~195 ℃ in the middle area, and 185~190 ℃ at the extruder head.
[0025] The present invention effectively improves the interfacial compatibility between PLA and PBAT by optimizing the specific gravity of PLA, PBAT, and titanate, and can significantly improve the mechanical properties of polylactic acid; by regulating a certain specific gravity of talcum powder, it is distributed at the interface of PLA and PBAT to improve the compatibility of its interface, further optimizes the mechanical properties and melt fluidity of the polylactic acid composite material, and ensures the low cost and practicality of the polylactic acid composite material; more importantly, based on the addition of a certain specific gravity of PBAT toughening agent, titanate coupling agent, and triethyl citrate plasticizer, a composite polylactic acid material with stronger toughness and not easy to break is obtained, and the poor toughness and processing performance defects of the existing 3D printing polylactic acid material are effectively overcome, the operation is simple, the production cost is reduced, and it is easy to industrialize production. The preparation method of the present invention is simple, and the obtained toughened and modified polylactic acid 3D printing wire has good comprehensive performance.
[0026] Example 1 The preparation method of high-strength and high-toughness polylactic acid filament for 3D printing is as follows: S1. PLA and PBAT were placed in a vacuum oven and dried at 80°C for 12 h.
[0027] S2, mixing equal amounts of titanate and triethyl citrate in deionized water to form a mixed solution, wherein the concentrations of titanate and triethyl citrate are both 0.06 g / ml, and adjusting the pH to 5.5 with 99.8% acetic acid to obtain an S solution; S3, mix the PLA and PBAT dried in S1 in a high-speed mixer, spray the S solution evenly during the mixing process, add talcum powder while spraying, stir at a speed of 400 rpm, stir for 3 hours, and continue stirring until completely uniform after spraying to obtain granules; In the whole process, based on weight parts, PLA is 95 weight parts, PBAT is 5 weight parts, talc is 1 weight part, titanate is 2 weight parts, and triethyl citrate is 4 weight parts.
[0028] S4. Dry the obtained granular material in a vacuum oven at 70° C. for 1 h to obtain dry granular material.
[0029] S5. The dried granular material is placed in a twin-screw extruder for blending, extrusion and wire drawing. The screw speed in the twin-screw extruder is 30 rpm. When feeding, the screw speed starts from 5 rpm and gradually increases to the maximum speed. It is divided into three areas, which are set to 160°C at the feeding port, 185°C in the middle area, and 190°C at the extruder head, respectively, to obtain high-strength and high-toughness polylactic acid filaments for 3D printing.
[0030] The diameter of the extruded wire is controlled at 1.7-1.75 mm.
[0031] The test samples were printed using a TuoZhu 3D printer (P1S model), with a printing temperature of 220 °C, a base plate temperature of 65 °C, a filling rate of 100%, and the rest being default parameters of the device.
[0032] Example 2 The preparation method of high-strength and high-toughness polylactic acid filament for 3D printing is as follows: S1. PLA and PBAT were placed in a vacuum oven and dried at 70°C for 15 h.
[0033] S2, mixing equal amounts of titanate and triethyl citrate in deionized water to form a mixed solution, wherein the concentrations of titanate and triethyl citrate are both 0.12 g / ml, and adjusting the pH to 6 with 98% acetic acid to obtain an S solution; S3, mixing the PLA and PBAT dried in S1 in a high-speed mixer, spraying the S solution evenly during the mixing process, adding talcum powder while spraying, stirring at a speed of 500 rpm, stirring for 2.5 h, and continuing to stir until completely uniform after spraying to obtain a filler; In the whole process, based on weight parts, PLA is 90 weight parts, PBAT is 10 weight parts, talc is 3 weight parts, titanate is 2.5 weight parts, and triethyl citrate is 2.5 weight parts.
[0034] S4. Dry the obtained filler in a vacuum oven at 80° C. for 1.5 h to obtain dry granular material.
[0035] S5. The dried granular material is placed in a twin-screw extruder for blending, extrusion and wire drawing. The screw speed in the twin-screw extruder is 40 rpm. When feeding, the screw speed starts from 10 rpm and gradually increases to the maximum speed. It is divided into three areas, which are set to 170 °C at the feeding port, 195 °C in the middle area, and 195 °C at the extruder head, respectively, to obtain high-strength and high-toughness polylactic acid filaments for 3D printing.
[0036] The diameter of the extruded wire is controlled at 1.7-1.75 mm.
[0037] The test samples were printed using a TuoZhu 3D printer (P1S model), with a printing temperature of 220 °C, a base plate temperature of 65 °C, a filling rate of 100%, and the rest being default parameters of the device.
[0038] Example 3 The preparation method of high-strength and high-toughness polylactic acid filament for 3D printing is as follows: S1. PLA and PBAT were placed in a vacuum oven and dried at 90°C for 13 h.
[0039] S2, mixing equal amounts of titanate and triethyl citrate in deionized water to form a mixed solution, wherein the concentrations of titanate and triethyl citrate are both 0.01 g / ml, and adjusting the pH to 5.8 with 97% acetic acid to obtain an S solution; S3, PLA and PBAT dried in S1 are mixed with talcum powder in a high-speed mixer, and S solution is evenly sprayed during the mixing process, and talcum powder is added while spraying. The stirring speed is 600 rpm, and the stirring time is 2 h. After spraying, stirring is continued until it is completely uniform to obtain granular material; In the whole process, based on weight parts, PLA is 85 weight parts, PBAT is 20 weight parts, talc is 5 weight parts, titanate is 3 weight parts, and triethyl citrate is 3 weight parts.
[0040] S4. Dry the obtained granules in a vacuum oven at 75° C. for 2 h to obtain dry granules.
[0041] S5. The dried granular material is placed in a twin-screw extruder for blending, extrusion and wire drawing. The screw speed in the twin-screw extruder is 35 rpm. When feeding, the screw speed starts from 15 rpm and gradually increases to the maximum speed. It is divided into three areas, which are set to 165°C at the feeding port, 190°C in the middle area, and 192°C at the extruder head, respectively, to obtain high-strength and high-toughness polylactic acid filaments for 3D printing.
[0042] The diameter of the extruded wire is controlled at 1.7-1.75 mm.
[0043] The test samples were printed using a TuoZhu 3D printer (P1S model), with a printing temperature of 220 °C, a base plate temperature of 65 °C, a filling rate of 100%, and the rest being default parameters of the device.
[0044] The ultimate spheres of the 3D printing filaments prepared in Examples 1 to 3 can all be printed completely and smoothly, with smooth discharge, no clogging or warping, and show good fluidity in microneedle array printing without the occurrence of wire drawing, indicating that the 3D printing filaments have good fluidity, toughness and strength.
[0045] Comparative Example 1 The preparation method of the high-strength and high-toughness 3D printed polylactic acid filament is the same as that of Example 1, except that: In S3, based on parts by weight, PLA is 95 parts by weight, PBAT is 4 parts by weight, talc is 5 parts by weight, titanate is 4 parts by weight, and triethyl citrate is 2 parts by weight.
[0046] The remaining steps and process parameters are the same as those in Example 1.
[0047] The ultimate sphere of the 3D printing filament prepared by the comparative method: the sphere can be printed completely, but a small amount of granular aggregates appear on the surface of the sphere, the material is discharged smoothly, there is no clogging or warping, and a large amount of wire drawing occurs in the microneedle array printing, indicating that the printing effect of the 3D printing filament is poor.
[0048] Comparative Example 2 The preparation method of the high-strength and high-toughness 3D printed polylactic acid filament is the same as that of Example 2, except that: In S3, based on parts by weight, PLA is 100 parts by weight, PBAT is 10 parts by weight, talc is 6 parts by weight, titanate is 4 parts by weight, and triethyl citrate is 4 parts by weight.
[0049] The remaining steps and process parameters are the same as those in Example 2.
[0050] Comparative Example 3 The preparation method of the high-strength and high-toughness 3D printed polylactic acid filament is the same as that of Example 3, except that: In S3, based on parts by weight, PLA is 80 parts by weight, PBAT is 20 parts by weight, talc is 10 parts by weight, titanate is 4 parts by weight, and triethyl citrate is 3 parts by weight.
[0051] The remaining steps and process parameters are the same as those in Example 3.
[0052] The ultimate sphere of the 3D printing filament obtained by the preparation method of Comparative Examples 2~3: the sphere can be printed completely, but a large amount of granular aggregates appear on the surface of the sphere, the discharge is not smooth, some of the spheres are blocked and warped, and wire drawing occurs in the microneedle array printing, indicating that the printing effect of the 3D printing filament is average.
[0053] The performance of the high-strength and high-toughness 3D-printed polylactic acid filaments prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was further verified, and the results are shown in Table 1 below: Table 1 Performance of 3D printed products obtained in Examples 1 to 3 and Comparative Examples 1 to 3
[0054] It can be seen from Table 1 that the tensile strength and elongation at break of the products obtained in Examples 1 to 3 are better than those of the products obtained in the corresponding comparative examples, indicating that the addition of low-content titanate can effectively play a good role in improving the interface; the melt index of the products obtained in Examples 1 to 3 is also better than that of the products obtained in the corresponding comparative examples, indicating that the addition of high-content talcum powder cannot effectively promote the improvement of fluidity, and when the content is less than 3%, it can play a good promoting role; the impact strength of the products obtained in Examples 1 to 3 is better than that of the products obtained in the corresponding comparative examples, indicating that the addition of triethyl citrate can effectively improve the notched impact performance of 3D printed products.
[0055] pass Figure 1 It can be seen from the DSC heating curve analysis diagram that by optimizing the ratio of PBAT, triethyl citrate, titanate and talc, the PLA composite crystallization performance can be significantly improved. No cold crystallization peak appears during the heating and melting process, and the highest crystallinity reaches 33.4%.
[0056] Therefore, compared with pure PLA 3D printed products, by adjusting the ratio of PBAT, triethyl citrate, titanate and talc to produce a synergistic effect, the elongation at break of 3D printing wire can be significantly improved within a specific proportion range, the melt index, crystallinity and tensile strength can be enhanced, the processing performance can be improved, and the application prospects are broad.
Claims
1. High-strength and high-toughness polylactic acid filament for 3D printing, characterized in that: The invention comprises the following components by weight percentage: 89-89.6 wt % of PLA, 4.5-4.9 wt % of PBAT, 2.7-4.3 wt % of titanate, 1.7-2.3 wt % of triethyl citrate and 2.3-3.5 wt % of talc.
2. The method for preparing high-strength and high-toughness 3D printed polylactic acid filaments according to claim 1, characterized in that: The specific method is as follows: S1. Place PLA and PBAT in a vacuum oven to dry; S2, mixing equal amounts of titanate and triethyl citrate in deionized water to form a mixed solution, and adjusting the pH to 5.5-6 with acetic acid to obtain S solution; S3, mixing the PLA and PBAT dried in S1 with talcum powder in a high-speed mixer, spraying S solution during the mixing process, stirring evenly, to obtain granular material; S4, drying the granular material obtained in S3 in a vacuum box to obtain dry granular material; S5. The dried granular material is placed in a twin-screw extruder for blending, extrusion and wire drawing to obtain a high-strength and high-toughness polylactic acid filament for 3D printing.
3. The method for preparing high-strength and high-toughness 3D-printed polylactic acid filament according to claim 2, characterized in that: The drying temperature in the vacuum oven in S1 is 70-90° C., and the blast drying time is 12-15 hours.
4. The method for preparing high-strength and high-toughness 3D printed polylactic acid filament according to claim 2, characterized in that: The titanate concentration in the S solution is 0.06 g / ml-0.12 g / ml, the triethyl citrate concentration is 0.06 g / ml-0.12 g / ml, and the acetic acid concentration is 97%-99.8%.
5. The method for preparing high-strength and high-toughness 3D printed polylactic acid filament according to claim 2, characterized in that: In S3, based on parts by weight, the PLA is 85-95 parts by weight, the PBAT is 5-20 parts by weight, the talc is 1-5 parts by weight, the titanate is 2-3 parts by weight, and the triethyl citrate is 2-3 parts by weight.
6. The method for preparing high-strength and high-toughness 3D printed polylactic acid filament according to claim 2, characterized in that: In the S3, the stirring speed is 400-600 rpm, and the stirring time is 2-3 h.
7. The method for preparing high-strength and high-toughness 3D-printed polylactic acid filament according to claim 2, characterized in that: The drying temperature in the vacuum box in S4 is 70-80° C., and the drying time is 1-2 hours.
8. The method for preparing the high-strength and high-toughness 3D-printed polylactic acid filament according to claim 2, characterized in that: The screw speed of the twin-screw extruder in S5 is 30-40 rpm, the screw speed during feeding is 25-35 rpm, the temperature of the feeding port of the extruder is 160-170°C, the temperature of the middle area of the extruder is 185-195°C, and the temperature of the extruder head is 190-195°C.
Citation Information
Patent Citations
Preparation method of polylactic acid material for 3D (three-dimensional) printing
CN103665802A
Reactive extrusion toughening carbon fiber reinforced polylactic acid 3D printing material and preparation method thereof
CN106867213A
Toughened polylactic acid 3D printing extrusion wire and preparation method thereof
CN110655767A